DNA damage-induced accumulation of centrosomal Chk1 contributes to its checkpoint function - Löffler, Harald; Bochtler, Tilmann; Tews, Britta; Tews, Björn; Ho, Anthony Dick; Lukas, Jiri; Bartek, Jiri; Krämer, Alwin (Cell cycle, 2007)
The checkpoint kinase Chk1 is an established transducer of ATR- and ATM-dependent signalling in response to DNA damage. In addition to its nuclear localization, Chk1 localizes to interphase centrosomes and thereby negatively regulates entry into mitosis by preventing premature activation of cyclin B-Cdk1 during unperturbed cell cycles. Here, we demonstrate that DNA damage caused by ultraviolet irradiation or hydroxyurea treatment leads to centrosomal accumulation of endogenous Chk1 in normal human BJ fibroblasts and in ATR- or ATM-deficient fibroblasts. Chemical inhibition of ATR/ATM by caffeine led to enhanced centrosomal Chk1 deposition associated with nuclear Chk1 depletion. In contrast to normal or ATM-deficient fibroblasts, genetically ATR-deficient Seckel-fibroblasts showed detectable constitutive centrosomal accumulation of Chk1 even in the absence of exogenous insults. After DNA damage, the centrosomal fraction of Chk1 was found to be phosphorylated at ATR/ATM phosphorylation sites. Forced immobilization of kinase-inactive but not wild-type Chk1 to centrosomes resulted in a G2/M checkpoint defect. Finally, both DNA damage, and forced centrosomal expression of Chk1 in the absence of genotoxic treatments, induced centrosome amplification in a subset of cells, a phenomenon which could be suppressed by inhibition of ATM/ATR-mediated signaling. Taken together, our results suggest that accumulation of phosphorylated Chk1 at centrosomes constitutes an additional element in the DNA damage response. Centrosomal Chk1 induces G2/M cell cycle arrest and may evoke centrosome amplification, the latter possibly providing a backup mechanism for elimination of cells with impaired DNA damage checkpoints operating earlier during the cell cycle.
Gesehen am 20.10.2021